Fresh and hardened properties of alkali-activated slag concrete: The effect of fly ash as a supplementary precursor. (10th October 2022) - Sun, Yubo; Liu, Zhiyuan; Ghorbani, Saeid; Ye, Guang; De Schutter, Geert
Abstract: The present study explores the possibility of replacing blast furnace slag (BFS) with coal fly ash (FA) to produce alkali-activated material (AAM) concrete with hybrid precursors. With an increased FA replacement ratio, the reaction kinetics, fresh and hardened properties of AAM mixtures have been investigated. The retardation effect on the reaction kinetics with an increased FA content has been observed, which not only extended the induction period along with the heat flow evolution but also reduced the cumulative heat release up to 24 h. Spherical FA particles can provide a ball-bearing effect to improve the workability of the hybrid AAM mixtures, while FA also slows down the deterioration of fresh properties since they are less reactive compared to BFS particles. Regarding the strength development, FA results in the reduction at all curing ages in the mixtures with a low silicate modulus (Ms0.25). Similarly, reduction in 1-day compressive strength has been detected in high silicate modulus mixtures (Ms0.5) with FA replacement, while the mixture with 10% FA exhibits the highest compressive strength among Ms0.5 concretes at later curing ages. Bigger capillary pores have been detected in AAM mixtures with an increase in FA content. However, AAM with 10% FA shows the lowest porosity in Ms0.5 mixtures, which is in agreement with the compressive strength results.